Improving same-day antiretroviral therapy in Botswana: effects of a multifaceted national intervention. (15th March 2022) - Montebatsi, Milton; Lavoie, Marie-Claude C.; Blanco, Natalia; Marima, Reson; Sebina, Kagiso; Mangope, Justin; Ntwayagae, Ookeditse; Whittington, Anna; Letebele, Mpho; Lekone, Phenyo; Hess, Kristen L.; Thomas, Vasavi; et al.
Abstract : Background: In 2019, the Botswana Ministry of Health and Wellness (MOHW) implemented an HIV national Reboot program, which was needed for refocusing and intensifying efforts for achieving epidemic control. The strategies deployed as part of Reboot were reviewed and evaluated for their effect on same-day and within-seven-days (fast-track initiation) antiretroviral therapy (ART) initiation among adults newly identified with HIV. Methods: We conducted a retrospective cohort analysis of patients aged 18 years or older who were newly diagnosed with HIV from October 2018 to September 2019 across 41 health facilities. We used generalized linear mixed models, adjusting for clustering by facility, to assess the association of the Reboot with same-day or within-seven-days ART initiation (fast-track initiation). Results: From October 2018 to January 2019, 28% (636/2269) of newly diagnosed HIV patients were initiated the same day of diagnosis, and 56% (1260/2269) were initiated within seven days. Following the launch of Reboot (February to September 2019), 59% (2092/3553) were initiated the same day of diagnosis, and 77% (2752/3553) were initiated within seven days. Clients were 2.08 (adjusted risk ratio 95% confidence interval 1.79–2.43) times more likely to be initiated the same day of diagnosis and 1.39 (adjusted risk ratio 95% confidence interval 1.28–1.52) times more likely to be initiated within seven days than before Reboot after adjusting for sex and age. Conclusion: In Botswana, a multifaceted national intervention improved timely ART initiation. Identifying and implementing different client-centered strategies to facilitate ART initiation is critical to preventing AIDS-related complications and prevent ongoing transmission.